1993
DOI: 10.1017/s003118200006710x
|View full text |Cite
|
Sign up to set email alerts
|

The effects of vector control on the antibody response to antigens ofOnchocerca volvulus

Abstract: The effects of exposure to infective larvae on the antibody response to a cocktail of specific recombinant antigens of Onchocerca volvulus and to a worm extract were evaluated by comparing the responses of individuals from a vector controlled area with those from an area of continuing transmission by ELISA. Individuals from the vector controlled areas were found to have reduced responses to both antigen preparations. A microfilerdermic (mf-) individuals from the area of vector control exhibited significantly l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

1994
1994
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 27 publications
1
6
0
Order By: Relevance
“…2 Our previous work has indicated that community antibody levels decreased after both vector control and treatment with ivermectin. 6,12 This, when combined with the results shown here, indicates that this test is sensitive to levels of infection within a community and that it will be possible to monitor the increase (or decrease) of these parameters effectively. Perhaps the best method for defining reinfection within a community is to measure incidence of infection, i.e., new infections.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…2 Our previous work has indicated that community antibody levels decreased after both vector control and treatment with ivermectin. 6,12 This, when combined with the results shown here, indicates that this test is sensitive to levels of infection within a community and that it will be possible to monitor the increase (or decrease) of these parameters effectively. Perhaps the best method for defining reinfection within a community is to measure incidence of infection, i.e., new infections.…”
Section: Discussionsupporting
confidence: 56%
“…2 Since this test is highly specific, 6,7 infections with other nematodes, frequently coendemic with O. volvulus, especially other human filarial parasites, do not affect the results. We have also shown that responses to this assay decrease in a community after vector control 6 and are beginning to decrease two years post-ivermectin treatment. 8 If antibody detection assays are sensitive to the endemicity/intensity of infection in a community, it may be possible to calibrate the assay and provide a serologic index (SI).…”
mentioning
confidence: 65%
“…What is clear from these investigations is that the antibody response is strong and diverse, immunoglobulin (Ig)G4 constitutes the predominant IgG subclass and high levels of IgE are present (7–9). Several recombinant O. volvulus antigens also induce this characteristic IgG4/IgE response (10–12). This isotype balance indicates the production of cytokines such as IL‐4 and IL‐13: in fact, cellular studies have demonstrated Th2 cytokine production in infected people (13,14).…”
Section: Introductionmentioning
confidence: 99%
“…This lack of association was to be expected in the case of OvMBP/lO and OvMBP/l 1 due to their localization in adult and L3 stages, but the localization of OvMBP/29 has yet to be established. An association between exposure to infective larvae and antibody titres to the cocktail of recombinant proteins has been indicated in areas under vector control (Bradley et al 1993b) indicating that differences in exposure to L3 larvae between individuals may account for some of the variation in responses shown here.…”
Section: Discussionmentioning
confidence: 71%